Evaluation of the RPPH System at RA Arafat Reksoniten 2022 - Latifah, Nurul; Darsinah, Darsinah (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2023)
RPPH is a system, so each RPPH component must be functionally related. This research aimed to evaluate the interrelationships of the elements in the RPPH. This research is a qualitative descriptive study. The method of collecting data used RPPH documents, and data analysis used content analysis. This research was conducted at RA Arafat Reksoniten Surakarta. The results showed that not all of the RPPH prepared by the teacher were functionally related.